Occupational health factors associated with work ability among early childhood education teachers - Ivana Nikolić; Snježana Mraković; Marko Badrić (Frontiers in Public Health, 2026)
Background Musculoskeletal disorders and psychosocial stressors are highly prevalent among early childhood education (ECE) teachers and may adversely affect work ability. This study examined occupational health factors associated with work ability among Croatian ECE teachers, with particular focus on musculoskeletal pain, work-related functional limitations, and exposure to work-related stressors. Methods A cross-sectional online survey was completed by 472 early childhood education (ECE) teachers. Measures included musculoskeletal pain across six body regions, work-related functional limitations, work-related stressors, physical activity, and an adapted single-item measure of current work ability. Hierarchical regression analyses were used to examine occupational health factors associated with work ability, and mediation analyses (PROCESS, 5,000 bootstrap samples) were conducted to examine indirect associations. Results Work-related functional limitations and exposure to work-related stressors showed the strongest negative associations with work ability. Musculoskeletal pain was not independently associated with work ability in the final regression model, but mediation analyses were statistically consistent with indirect associations via functional limitations and work-related stressors. Teachers who met WHO physical activity recommendations reported slightly higher work ability and more favorable occupational health indicators, although physical activity was not independently associated with work ability. Conclusion Work ability among early childhood education (ECE) teachers was most closely associated with work-related functional limitations and work-related stressors. Musculoskeletal pain was not independently associated with work ability, although the mediation analyses were statistically consistent with indirect associations via functional limitations and work-related stressors. These findings highlight the importance of considering both physical and psychosocial aspects of occupational health when addressing work ability in ECE settings. Given the cross-sectional design, the observed associations should not be interpreted as causal.